Tracing the Past: Exploring the Link Between Past Tense Mastery and Students’ Written in EFL Learners - Saiful (Acitya: Journal of Teaching and Education, 2025)
This study aims to explore the relationship between students’ mastery of past tense and their ability to write about past experiences. A total of 40 eleventh-grade students participated in the research. Data were collected through two written assessments: a grammar test focusing on past tense usage and a writing task that required students to retell a story using appropriate tenses. The grammar test included multiple-choice questions and sentence transformation items, while the writing task offered four topics from which students chose one. The results of the grammar test revealed a mean score of 4.3, which falls into the “Poor” category. This indicates that students generally struggle with understanding and applying past tense forms correctly. On the other hand, the writing assessment showed a mean score of 6.9, classified as “Fairly Good.” This suggests that, despite limited grammar mastery, students were moderately successful in expressing ideas about past events in written form. To determine the strength of the correlation between the two variables, the Pearson Product-Moment Correlation Coefficient was applied. The analysis resulted in an r-value of 0.497, indicating a moderate positive correlation between past tense mastery and writing performance. These findings highlight the importance of integrating targeted grammar instruction with writing practice to enhance students’ overall writing proficiency, particularly in expressing past experiences.